(untitled) (Nexus International Journal of Science and Education, 2024)
The study unfolded the extent of practical skills of instruction and its correlation with literacy development stages in Matina District, Davao City Division. The study used non-experimental descriptive-correlational research design, where it utilized adapted survey instrument to gather responses from the randomly selected teacher-respondents. Data gathered were treated using Mean scores with descriptive interpretation, Pearson r and Simple Linear Regression Analysis. Findings revealed that teachers’ practical skills of instruction in terms of fluency, vocabulary development, reading comprehension, spelling, composition, consensus findings of research, decoding, word attack and concepts of print, letter recognition phoneme awareness is extensive, while, learners’ literacy development stages in terms of intermediate reading, advanced reading, emergent literacy, alphabetic fluency, words and patterns are moderately extensive. There is a significant relationship between teachers’ practical skills of instruction and learners’ literacy development stages. Domains of practical skills of instruction in terms of concepts of print, letter recognition, phoneme awareness, decoding, word attack, spelling, fluency and reading comprehension significantly influenced literacy development. Future research may impact of classroom factors, such as classroom environment, classroom management strategies, and teacher-student interactions, on learners' literacy development. Investigate how these factors interact with practical skills of instruction and their combined effect on student outcomes. Investigate the extent to which teacher preparation programs equip educators with the necessary practical skills of instruction for effective literacy development. Identify areas of improvement and propose recommendations for enhancing teacher training in this domain.